2021
DOI: 10.1093/jac/dkab062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-existing drug resistance on risk of virological failure in South Africa

Abstract: Objectives There is conflicting evidence on the impact of pre-existing HIV drug resistance mutations (DRMs) in patients infected with non-B subtype virus. Methods We performed a case–cohort substudy of the AIDS Drug Resistance Surveillance Study, which enrolled South African patients initiating first-line efavirenz/emtricitabine/tenofovir. Pre-ART DRMs were detected by Illumina sequencing of HIV pol and DRMs present at &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…An increased likelihood of VF among people with PDR on EFV/XTC/TDF was also observed in 2 recent large studies: a the phase 3, randomized clinical trial comparing TAF/FTC/DTG, TDF/FTC/DTG or TDF/FTC/EFV for first-line treatment of HIV-1 infection (ADVANCE) [ 44 ], in which VS among those with and without PDR was 65% and 85%, respectively ( P < .001), and a case-cohort substudy of the HIV/AIDS Drug Resistance Surveillance Study (ADReSS), enrolling 1000 patients initiating first-line efavirenz/emtricitabine/tenofovir in KwaZulu-Natal, South Africa [ 45 ], in which PDR was associated with a 3-fold greater risk of VF ( P = .002).…”
Section: Discussionmentioning
confidence: 99%
“…An increased likelihood of VF among people with PDR on EFV/XTC/TDF was also observed in 2 recent large studies: a the phase 3, randomized clinical trial comparing TAF/FTC/DTG, TDF/FTC/DTG or TDF/FTC/EFV for first-line treatment of HIV-1 infection (ADVANCE) [ 44 ], in which VS among those with and without PDR was 65% and 85%, respectively ( P < .001), and a case-cohort substudy of the HIV/AIDS Drug Resistance Surveillance Study (ADReSS), enrolling 1000 patients initiating first-line efavirenz/emtricitabine/tenofovir in KwaZulu-Natal, South Africa [ 45 ], in which PDR was associated with a 3-fold greater risk of VF ( P = .002).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that individuals with preexisting low-frequency DRMs at baseline have the same DRMs at the time of VF. [40,41] However, other studies have found no association between baseline low-frequency DRMs and VF on cART. [40,42,43] Conflicting results on the clinical importance of low-frequency DRMs indicate the need for further investigations on the clinical impact of low-frequency DRMs in different settings.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients entering the SENSE trial for first‐line ART in Europe, Russia, and Israel, 13.9% of patients presented with at least one polymorphic mutation in their baseline plasma (V90I, V106I, or E138A), without any impact on the virological outcomes of an etravirine‐based ART program 26 . In a South African cohort, the detection of drug‐resistant mutations alone, including E138A, did not predict an increased risk of virological failure 27 . Additionally, there was one patient in the Eviplera clinical trial, who presented with an E138A mutation at baseline and was shown to maintain virological suppression throughout Week 48 28…”
Section: Discussionmentioning
confidence: 97%
“… 26 In a South African cohort, the detection of drug‐resistant mutations alone, including E138A, did not predict an increased risk of virological failure. 27 Additionally, there was one patient in the Eviplera clinical trial, who presented with an E138A mutation at baseline and was shown to maintain virological suppression throughout Week 48. 28…”
Section: Discussionmentioning
confidence: 99%